Efficacy of stereotactic body radiation therapy for locoregional recurrent pancreatic cancer after radical resection - Ji, Xiaoqin; Zhou, Bin; Ding, Wei; Wang, Jiasheng; Jiang, Wanrong; Li, Yikun; Hu, Jun; Sun, Xiangdong (Frontiers in Oncology, 2022)
OBJECTIVE: This study aimed to analyze the efficacy and toxicity of stereotactic body radiotherapy (SBRT) for locoregional recurrent pancreatic cancer after radical resection. METHODS: Patients with locoregional recurrent pancreatic cancer after surgery treated with SBRT in our institution were retrospectively investigated from January 2010 to January 2020. Absolute neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) recorded at pretreatment were analyzed. Endpoints included overall survival (OS), progression-free survival (PFS) and cumulative incidences of local failure (LF) and metastatic failure (MF). RESULTS: A total of 22 patients received SBRT with a median prescribed dose of 40 Gy (range of 30-50 Gy)/4 to 7 fractions. The median OS of all patients was 13.6 months (95% CI, 9.6-17.5 months). 0-1 performance status (HR 12.10, 95% CI 2.04-71.81, P=0.006) and ≤ 2.1 pre-SBRT NLR (HR 4.05, 95% CI 1.21-13.59, P=0.023) were significant predictors of higher OS on multivariable analysis. The median progression-free survival (PFS) of the cohort was 7.5 months (95% CI, 6.5-8.5 months). The median time to LF and MF were 15.6 months and 6.4 months, respectively. The rate of MF as a first event was higher than that of first event LF. Pain relief was observed in all patients (100%) 6 weeks after SBRT. In terms of acute toxicity, grade 1 including fatigue (6, 27.3%), anorexia (6, 27.3%), nausea (4, 18.2%) and leukopenia (4, 18.2%) was often observed. No acute toxicity of grade 4 or 5 was observed. In terms of late toxicity, no treatment-related toxicity was found during follow-up. CONCLUSION: This study showed that SBRT can significantly reduce pain, effectively control local tumor progression, and have acceptable toxicity for patients with locoregional recurrence after radical resection of primary pancreatic cancer. Good performance status and lower pre-SBRT NLR were associated with improved overall survival.